Interpersonal Function on Tour Commentaries: A Modality Study - Krisna Yudha Bakhti; Zewitra Zewitra (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Functioned as a social medium, tour commentaries are used by tour guides to interact and communicate with tourists, especially in explaining activities, locations, cultures, and knowledge regarding the place they are visiting. These commentaries bring interpersonal function that is realized through the use of modality. This current study, therefore, aims to (1) identify the use of modalities that bear the interpersonal function found in students’ tour commentaries and (2) describe the meaning of the modalities used. This study employed descriptive qualitative and text analysis methods using Halliday’s theory of modality. The data, 57 utterances containing modality, were obtained from tour commentaries of Tour and Travel Business Study Program’s students of Politeknik Negeri Bandung. This study reveals the use of both modalization, to show ’probability’ and ’usuality’, and modulation, to show ’obligation’ and ’inclination’, on students’ tour commentaries. The ’probability’ and ’obligation’ functions are most discovered. The results can be beneficial academically and practically. They can give insight into how tour guides apply modality in their tour commentaries.     Keywords: modality, modalization, modulation, tour commentaries